2016
DOI: 10.1038/cddis.2016.315
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 DEAD-box RNA helicase plays a central role in mitochondrial protein quality control in Leishmania

Abstract: DDX3 is a highly conserved member of ATP-dependent DEAD-box RNA helicases with multiple functions in RNA metabolism and cellular signaling. Here, we describe a novel function for DDX3 in regulating the mitochondrial stress response in the parasitic protozoan Leishmania. We show that genetic inactivation of DDX3 leads to the accumulation of mitochondrial reactive oxygen species (ROS) associated with a defect in hydrogen peroxide detoxification. Upon stress, ROS production is greatly enhanced, causing mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 60 publications
(91 reference statements)
1
51
0
Order By: Relevance
“…Polypeptides modified with K48‐linked polyubiquitin chains, which also serve as a major targeting signal for the proteasome (Chau et al, ), are physiological substrates for VCP. Our previous studies revealed Li VCP association with several proteasome subunits (Padmanabhan et al, ). The partial colocalisation of Li VCP with the ER and its weaker association with the mitochondrion, as suggested by indirect immunofluorescence studies, are in line with Li VCP being involved in the extraction of polyubiquitinated proteins from cellular organelles for subsequent proteasomal degradation, as described in other eukaryotes (Qi et al, ; Taylor & Rutter, ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Polypeptides modified with K48‐linked polyubiquitin chains, which also serve as a major targeting signal for the proteasome (Chau et al, ), are physiological substrates for VCP. Our previous studies revealed Li VCP association with several proteasome subunits (Padmanabhan et al, ). The partial colocalisation of Li VCP with the ER and its weaker association with the mitochondrion, as suggested by indirect immunofluorescence studies, are in line with Li VCP being involved in the extraction of polyubiquitinated proteins from cellular organelles for subsequent proteasomal degradation, as described in other eukaryotes (Qi et al, ; Taylor & Rutter, ).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, we tested whether parasite mutant lines with a significant decrease in VCP expression levels are more sensitive to proteasome inhibitors or to other stresses inducing proteotoxicity. Proteosome inhibition by MG‐132 is known to increase accumulation of polyubiquitinated proteins, also in Leishmania (Padmanabhan et al, ). Both the Li VCP (NEO/+) and the Li VCP (NEO/HYG) + VCP HA strains showed ~2‐fold higher sensitivity to MG‐132 than the WT strain (Figure S11a,c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular processes such as replication, transcription, posttranscriptional modification, translation, mRNA splicing and mRNA export and its stability are vital for living organisms, and helicase enzymes are to play very crucial role in gene expression and regulation (Hartman et al, 2006;Bolinger et al, 2007;Bolinger et al, 2010;Górna et al, 2010;Ranji et al, 2011;Andreou and Klostermeier, 2013;Chu et al, 2016;Lin et al, 2016;Padmanabhan et al, 2016). Helicase enzymes are categorized into two types namely, DNA helicase and RNA helicase (Jankowsky, 2011).…”
Section: Rna Helicasesmentioning
confidence: 99%
“…Clear supernatants were further incubated with Protein G anti-HA magnetic beads at 4°C for 4 h on a gentle rotator. Beads were then washed by TBS-0.05% Tween (SigmaAldrich) three times (30 sec each) by gentle agitation and subjected to LC-MS/MS analysis as previously described (Padmanabhan et al 2016). Immunoprecipitation experiments were done on cotransfected parasites as above except that prior to freezing the parasites in liquid nitrogen, they were exposed to 400 mJ/cm 2 UV irradiation on a Stratalinker 2400 UV crosslinker in PBS medium and then immediately harvested and snap-frozen.…”
Section: Immunoprecipitation and Mass Spectrometry Analysismentioning
confidence: 99%